"CONSTITUTIONAL TENDENCIES IN FORMING THE LEGAL AWARENESS OF YOUTH" - Akramov Kozimjon Ibragimjon o‘g‘li; Rutamova Nozima Yuldashaliyevna (Western European Studies, 2025)
This in the article in our country youth fold legal consciousness and literacy , youth constitution norms and the rules where at the level knowledge and him/her to life done increase potential about word goes
Keywords: Youth; constitution; citizen